2022
DOI: 10.3389/fonc.2022.897495
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Chemotherapy Drug Bevacizumab May Induce Muscle Atrophy Through CDKN1A and TIMP4

Abstract: The muscle in the organism has the function of regulating metabolism. Long-term muscle inactivity or the occurrence of chronic inflammatory diseases are easy to induce muscle atrophy. Bevacizumab is an antiangiogenic drug that prevents the formation of neovascularization by inhibiting the activation of VEGF signaling pathway. It is used in the first-line treatment of many cancers in clinic. Studies have shown that the use of bevacizumab in the treatment of tumors can cause muscle mass loss and may induce muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…However, some studies also indicated that the low expression of CDKN1A was associated with the proliferation of fibroblast-like synoviocytes which is one of the manifestations of KOA [ 80 ]. In sarcopenia, CDKN1A contribute to the age-associated decrease in satellite cell proliferation, which causes the muscle atrophy [ 81 ]. CEBPB is an important transcription factor regulating the expression of genes involved in immune and inflammatory responses [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies also indicated that the low expression of CDKN1A was associated with the proliferation of fibroblast-like synoviocytes which is one of the manifestations of KOA [ 80 ]. In sarcopenia, CDKN1A contribute to the age-associated decrease in satellite cell proliferation, which causes the muscle atrophy [ 81 ]. CEBPB is an important transcription factor regulating the expression of genes involved in immune and inflammatory responses [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%